Altas habilidades : (re)construindo narrativas - Mattei, Giovana (2008)
This work had as objective to recognize children with high ability at outskirts environment, changing narratives and labels restricts of them, in order to develop your competence in scholar environment. The study detains two theories, carefully chosen for being in accordance with the proposal of the research: the theory of multiple intelligences of Howard Gardner and the theory of three rings of Joseph Renzulli, that approach important aspects about intelligences and high ability. The instruments used to collect the data to the teachers were the observation forms in classroom, adapted by Susana G. P. Barrera Pérez (2003), the forms with indicators of high ability, adapted by Larice Bonato Germani, Mara Nieckel da Costa and Nara Wellausen Vieira, from Scales for Rating the Behavior Characterstics of Superior Students by Joseph Renzulli, Linda Smith, Alan White, Carolyn Callahan and Robert Hartman (translated and adapted by Ângela M. R. Virgolim). Besides the questions, the teachers were interviewed with the intention of observe the narratives about the recognized students. To the students were applied questions of self-nomination, elaborated by Joseph Renzulli and Linda Smith, translated and adapted by Ângela Virgolim University of Brasília/Uconn. The discussion proposal involves the special education, however, the knowledge that professionals of education have about the high abilities don t exceed the common sense, generating the exclusion of the included, in other words, the students with high abilities are in schools, but often they evade or leave the school because they don t find subsidies to development of their abilities